A data-aided OFDM/OQAM synchronization algorithm using maximum posterior probability criterion - Chen, Hao; Hu, Su; Wu, Gang; Li, Shaoqian (ICCTA 2011 : IET International Conference on Communication Technology and Application : 14-16 October 2011, 2011)
The OFDM/offset QAM (OFDM/OQAM) systems are sensitive to synchronization errors. To overcome this shortage of OFDM/OQAM systems, in this paper, a data-aided joint symbol timing and carrier frequency offsets (CFO) estimation algorithm based on maximum posterior probability criterion is proposed. Compared to traditional data aided algorithms, the derived algorithm achieves better performance in multipath fading channels in terms of capture probability of symbol timing offsets, root mean square error (RMSE) of CFO estimation and bit error rate (BER) versus signal-to noise power ratio (SNR).